The associated risk factors for underweight and overweight high school students in Cambodia. Issue 5 (September 2018) - Yen, Yat; Shi, Yumin; Soeung, Bunly; Seng, Ratny; Dy, Channy; Suy, Rathny; Ngin, Kimlong
Highlights: Of 3, 806 students, 47.4% and 2.3% were underweight and overweight respectively. Both underweight and overweight students were vulnerable to substance use, feeling depressed, and violent behaviors. Sleep deficiency was high for underweight students while feeling lonely and suicide attempts were the critical risks for overweight students. Eating fruit/vegetable daily and physical activity were protective factors against underweight and overweight epidemics. Abstract: Purpose: Overweight and underweight are one of the leading risk factors for non-communicable diseases (NCDs), but little research on this area has been undertaken in Cambodia. Therefore, this study aimed to measure underweight and overweight and their associated risk behaviors among Cambodian high school students. Methods: 3806 students (mean ag = 15.65 years, SD = 1.80, age range = 11–18 years) from the 2013 Cambodia-Global School-based Student Health Survey were used to yield representative samples of the Cambodian students. Body Mass Index (BMI) was assessed by students' self-reported height and weight. The substance use, depression, eating behaviors, suicidal ideation, and violence were examined as risk factors. The Chi-square and multinomial regressions were performed to assess the relationships between risk factors and BMI. Results: The prevalence of underweight was 47.4% (N = 1805, Male = 23.3%vs.24.1%) and overweight was 2.3% (N = 89, Male = 1.0%vs.1.3%). The BMI was significantly controlled by age, gender, and body height. Both underweight and overweight students were significantly vulnerable to substance use, feeling depressed, and violent behaviors. Of the risk factors, shortest sleep was prevalent for underweight students while feeling lonely and suicide attempts were the critical risks for overweight students. The daily fruit/vegetable consumption and physical activity were good preventive factors of both underweight and overweight epidemics. Conclusions: The risk behaviors of students appear to be strongly associated with underweight and overweight. Interventions targeting these risk behaviors may have the potential to reduce risks. Meanwhile, the preventive strategies should focus on vulnerable students who have poor academic performance, mental health issues and a history of violent experiences.